Studies on Progeny Performance, Variability, Heritability, Genetic Gain and Correlation in Ulmus Villosa Brandis at Seedling Stage - Thakur, I. K.; Thakur, Sapna; Singh, N. B.; Gupta, R. K.; Sharma, J. P.; Sankanur, M. (Indian Forester, 2014)
The present study on Ulmus villosa was carried out in Himachal Pradesh to know the progeny performance and estimate genetic variability for biomass traits of progenies at nursery stage. Seeds were collected from five mother trees each at six seed sources and progenies were raised. All the biomass characters varied significantly among different seed sources and trees within seed source. Root dry weight was found to have higher coefficient of variability, whereas shoot dry weight and shoot fresh weight had higher heritability with moderate genetic gain suggesting their importance for the success of improvement through selection. Genotypic and phenotypic correlations for all possible pairs were also found out and discussed. Highly significant and positive genotypic and phenotypic correlations were observed for fresh shoot weight with fresh root weight and fresh shoot weight with dry shoot weight indicating their significance in the indirect selection.